New Resources For Smart Food Retail Mapping. A Gis And The Open Source Perspective - Vaz, Eric; Khaper, Monica (Journal of Tourism, Sustainability and Well-being, 2016)
In this paper it is demonstrated that open-source GIS software may contribute to allow non-profit organizations and local food retailers to strategically locate food shops. This impacts realtors and other businesses as well. Areas are covered and clients served avoiding food deserts and increasing security in the health sector (Barnes et al., 2016). The methodology demonstrates how mapping may be processed, allowing people to get a good understanding of the food distribution. Also, decision making at corporate level improves due to better connecting to local production and organic retailers and to better reach out to local consumption. A major consequence of this exercise is likewise to educate users on the negative impacts of food deserts on health and improve awareness supporting the design and integration of sustainable and healthy lifestyles (Vaz and Zhao, 2016). This novel proposal that combines spatial and locational data visualization (McIver, 2003), as well as sharing of information of healthy food retailers within the urban nexus (Morgan and Sonnino, 2010) engage communities actively to participate in the integration of new consumer behaviours and make them clearly expressed.